2012
DOI: 10.1016/j.cell.2012.03.002
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Small RNAs in DNA Double-Strand Break Repair

Abstract: Eukaryotes have evolved complex mechanisms to repair DNA double-strand breaks (DSBs) through coordinated actions of protein sensors, transducers, and effectors. Here we show that ∼21-nucleotide small RNAs are produced from the sequences in the vicinity of DSB sites in Arabidopsis and in human cells. We refer to these as diRNAs for DSB-induced small RNAs. In Arabidopsis, the biogenesis of diRNAs requires the PI3 kinase ATR, RNA polymerase IV (Pol IV), and Dicer-like proteins. Mutations in these proteins as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
617
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 529 publications
(671 citation statements)
references
References 62 publications
(91 reference statements)
29
617
2
Order By: Relevance
“…Alternatively, phenotypic differences could be related to functions of AGO1 other than miRNA target repression. Indeed, the implication of AGO proteins in several pathways such as nonsense-mediated mRNA decay (Choe et al, 2010), alternative splicing (AmeyarZazoua et al, 2012;Yang et al, 2012b;Taliaferro et al, 2013;Alló et al, 2014), DNA double-strand break repair (Michalik et al, 2012;Wei et al, 2012), nucleosome occupancy at transcription start sites (Carissimi et al, 2015), and quality control of mRNAs encoding proteins entering the secretory pathway (Karamyshev et al, 2014) has been proposed during the last years. If that is the case, the conditional slicer-deficient alleles might be a valuable tool to investigate novel functions of plant AGO1 by decoupling these from target regulation.…”
Section: Slicer Activity In Mirna Biogenesis and Accumulationmentioning
confidence: 99%
“…Alternatively, phenotypic differences could be related to functions of AGO1 other than miRNA target repression. Indeed, the implication of AGO proteins in several pathways such as nonsense-mediated mRNA decay (Choe et al, 2010), alternative splicing (AmeyarZazoua et al, 2012;Yang et al, 2012b;Taliaferro et al, 2013;Alló et al, 2014), DNA double-strand break repair (Michalik et al, 2012;Wei et al, 2012), nucleosome occupancy at transcription start sites (Carissimi et al, 2015), and quality control of mRNAs encoding proteins entering the secretory pathway (Karamyshev et al, 2014) has been proposed during the last years. If that is the case, the conditional slicer-deficient alleles might be a valuable tool to investigate novel functions of plant AGO1 by decoupling these from target regulation.…”
Section: Slicer Activity In Mirna Biogenesis and Accumulationmentioning
confidence: 99%
“…The predominant sRNA species include microRNAs (miRNAs) generated by DCL1 Kurihara and Watanabe, 2004;Qi et al, 2005), trans-acting small interfering RNAs (ta-siRNAs) processed by DCL4 (Peragine et al, 2004;Vazquez et al, 2004;Gasciolli et al, 2005;Xie et al, 2005), and heterochromatic siRNAs (hc-siRNAs) produced by DCL3 (Xie et al, 2004;Qi et al, 2005;Henderson et al, 2006). Additional types of sRNAs including natural antisense siRNAs (Borsani et al, 2005), long siRNAs , long miRNAs (lmiRNAs) (Wu et al, 2010), double-strand-break (DSB)-induced sRNAs (diRNAs) (Wei et al, 2012), and DCL-independent siRNA (sidRNAs) (Ye et al, 2016) have also been discovered. While miRNAs, ta-siRNAs, and natsiRNAs mediate posttranscriptional gene silencing (PTGS), hc-siRNAs, lmiRNAs, and sidRNAs direct DNA methylation thus inducing transcriptional gene silencing (TGS).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, they induce the synthesis of non coding transcripts, which can be further processed into smaller RNA by components of the RNA interference machinery and together play a supportive role in DDR signaling (Francia et al, 2012), (Wei et al, 2012), (Michalik et al, 2012), . We recently reported that RNAPII is recruited to DSBs in a MRN-dependent manner, where it synthesizes dilncRNAs from and towards DNA ends.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, DROSHA inactivation by siRNA prevents telomere fusions. Other groups have reported an involvement of sequence-specific DICER dependent ncRNA in DNA repair by HR (Gao et al, 2014), (Wei et al, 2012) and knockdown of DICER or DROSHA significantly reduced accumulation of two major HR factors, Rad51 and BRCA1 to DSBs (Wang and Goldstein, 2016).…”
Section: Introductionmentioning
confidence: 99%